Optimization of Electrolytic Cleaning of Low Carbon Steels - Urréjola, Santiago R.; Garcíais, Javier Lora; Devesa-Rey, Rosa (European Journal of Sustainable Development, 2016)
Electrolysis is an effective method for recovering rusted pieces in acceptable times of operation without generating practically any residues and with a very low cost. The process is controlled by the concentration of electrolyte used, the current intensity selected and the operation time, among others. Knowing the best operating conditions allow cleaning the rusted parts more efficiently. In this work, it was carried out an optimization of the cleaning process by means of an incomplete 33 factorial design. The substrate selected consists of several low steel carbon probes (Fe>99.7%), which were subjected to oxidation in the laboratory to ensure homogeneity. The independent variables assayed included the concentration of the electrolyte employed (x1), the current intensity (x2) and the temperature of operation (x3), whereas the dependent variable was based on the weight differences of the probes after being subjected to the cleaning process. The results obtained showed that the optimal conditions for removing rust from low steel carbon were 5% of electrolyte, a current intensity of 3 A and a temperature of operation of 40 ºC. These results demonstrated the potential application of electrolytic cleaning combined to an optimization by means of a factorial design to restore low steel carbon pieces. Keywords: Oxidation; electrolytic; metal; cleaning; factorial design